Transcription factors that control development of the thymic microenvironment - Boehm, Thomas; Nehls, Michael; Kyewski, Bruno (Immunology today, 1995)
Very little is known about genetic determinants of thymic stromal cell differentiation. However, two genes involved in lineage commitment of the thymic stroma have recently been identified, representing a starting point in the genetic dissection of the lineage composition and phenotypic heterogeneity of the thymic microenvironment.